2021
DOI: 10.1007/s00391-021-01971-y
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes about very old people and perceived societal appreciation in very old age

Abstract: Background People in very old age (VOA) are expected to be confronted with particularly negative stereotypes. These influence societally shared behavior towards and judgements about them. Such external evaluations of individuals’ lives are considered a crucial part of their quality of life (QoL). Objective The present study elaborated a) the societal appreciation perceived by people in VOA and b) the stereotypes about people in VOA held by stakeholders fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…In this context, the finding that perceived attitudes explained 1.2% of the variance in life satisfaction presents a significant contribution to the existing literature on how older adults feel in old age. A previous study found that about 60% of older adults (80+) felt that they were rather not needed or not at all needed by society, and approximately 14% of them felt rather or strongly treated as a burden by society [ 40 ]. Though the feeling of being treated as a burden was highly predicted by health-related variables, their study did not cover the subjective well-being dimension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the finding that perceived attitudes explained 1.2% of the variance in life satisfaction presents a significant contribution to the existing literature on how older adults feel in old age. A previous study found that about 60% of older adults (80+) felt that they were rather not needed or not at all needed by society, and approximately 14% of them felt rather or strongly treated as a burden by society [ 40 ]. Though the feeling of being treated as a burden was highly predicted by health-related variables, their study did not cover the subjective well-being dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Raising awareness of negative attitudes and treatment of older adults, and consciously using this knowledge in the care of older fail persons might support an increased quality of life. The topic of stereotypes highlights the need to have a normative discussion about subjective well-being and finding ways to improve it [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants stated that it was not possible for them to generalise about persons above the age of 80, as they often saw patients who were active and healthy at this age, but they also saw patients under the age of 80 who needed complex care. In the study by Reissmann et al [40], the participants confirmed that older adults (≥ 80 years) are viewed as equally heterogeneous. Participants stated that the age of a person did not change individual differences.…”
Section: Discussionmentioning
confidence: 88%
“…Bei der Untersuchung dieser Stereotype in semistrukturierten Interviews mit unterschiedlichen Stakeholdern [12] wurde deutlich, dass die bevorzugten Werte hochaltriger Menschen teilweise im Kontrast zu vorherrschenden Alternsbildern stehen. Aufschlussreiche Unterschiede waren diesbezüglich zwischen solchen Akteuren zu verzeichnen, deren Arbeit in unmittelbarem Kontakt mit hochaltrigen Menschen erfolgt (Gruppe 1), und solchen, bei denen das nicht der Fall ist (Gruppe 2).…”
Section: Einordnung Ausgewählter Ergebnisseunclassified